PENERAPAN STRATEGI PEMASARAN DIGITAL TERHADAP PENINGKATAN PENJUALAN PRODUK PADA PT SURACOJAYA ABADI MOTOR DI KABUPATEN SIDENRENG RAPPANG - Sri Nurfadilla; Adam Latif; Andi Riska Andreani Syafaruddin; Haslindah, Haslindah (Journal of Innovation Research and Knowledge, 2025)
Digital marketing has become a crucial element in modern business strategies, including for PT Suracojaya Abadimotor, which faces the challenge of increasing sales amid intense competition. This study aims to explore the implementation of digital marketing strategies to enhance sales and build long-term relationships with consumers. Using a qualitative method through interviews, observations, and documentation, this research analyzes the application of strategies based on the marketing mix (4P) and the Commitment-Trust Theory to examine the relationship between marketing activities and sales growth. Sales improvement is influenced by trust, commitment, communication, shared values, empathy, and reciprocity between the company and customers. The results show that the company still faces several obstacles, such as infrequent content updates, slow responses to consumers, and issues related to stock and distribution. Digital strategies through Instagram and WhatsApp are considered quite effective in building trust and communication but remain suboptimal in boosting sales due to a lack of innovation and limited utilization of digital data. Social media serves more as an initial information platform rather than a primary transactional medium.